A measure of Turkey's sovereign and banking sector credit risk: Asset swap spreads - Doruk Küçüksaraç; Abdullah Kazdal; Halil İbrahim Korkmaz; Yiğit Onay (Central Bank Review (CBR), 2021)
The existence of the credit derivatives written on the eurobonds such as credit default swaps or asset swaps allows policymakers and investors to monitor the evolvement of credit risk. However, these instruments are mostly available in advanced economies, whereas the market for credit derivatives in emerging market countries, including Turkey, is limited in terms of liquidity and maturity. In this regard, this study aims to construct a proxy for the credit risk of the Turkish Treasury and banking sector in international markets by calculating asset swap spread for US dollar-denominated fixed coupon eurobonds, which requires a robust estimation of the relevant yield curves. The study firstly presents the estimation of the sovereign and banking sector yield curves and then constructs a synthetic asset swap structure to obtain embedded credit risk premia in the eurobond curves. Our findings show that the proposed credit risk indicator is vastly correlated with credit default swap premium. In addition to this, estimated eurobond curves are also useful for monitoring borrowing cost dynamics of the Turkish Treasury and banking sector in international markets.
Keywords: G12; G15; 330; Asset swap spread; Credit risk; Yield curve